2020
DOI: 10.1016/j.eclinm.2020.100625
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of cancer drugs: Comparative analysis of the United States and England

Abstract: Background: England's National Institute for Health and Care Excellence (NICE) and the US' Institute for Clinical and Economic Review (ICER) both conduct cost-effectiveness evaluations for new cancer drugs to help payers make drug coverage decisions. However, NICE and ICER assessments have been noted to reach different conclusions. We aim to better understand the degree to which their recommendations diverge and what drives these apparent differences. Methods: We compared the methods and results of publicly av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…7 Nonetheless, for some conditions such as in oncology, newly approved drugs are not proven to be cost-effective and thus caution must be taken when considering cancer therapies as ideal targets for value-based cost-sharing reform. 8 The current cost-sharing system also directly propagates health inequity. Theoretical evidence from health care economics suggests that cost-sharing schemes ought to be scaled in proportion to disposable income to maximize their effect.…”
mentioning
confidence: 99%
“…7 Nonetheless, for some conditions such as in oncology, newly approved drugs are not proven to be cost-effective and thus caution must be taken when considering cancer therapies as ideal targets for value-based cost-sharing reform. 8 The current cost-sharing system also directly propagates health inequity. Theoretical evidence from health care economics suggests that cost-sharing schemes ought to be scaled in proportion to disposable income to maximize their effect.…”
mentioning
confidence: 99%
“…The present study emphasizes the need for more RCTs and realworld evidence for clinical decision-making policies. 19 This is especially true for the nonepithelioid group in CM743, which was not prespecified in the protocol and should be considered hypothesis generating.…”
Section: Discussionmentioning
confidence: 99%
“…Ribociclib is not alone in this regard. A recent study assessed the cost-effectiveness evaluations of cancer drugs conducted by the US's Institute for Clinical and Economic Review (ICER), and found that most new cancer drugs were not cost-effective (40). In the US, regulatory approvals are not tied to costs and the complicated network of multiple payers in the healthcare system is associated with less negotiating power to obtain substantial drug discounts with manufacturers as compared to other countries with single-payer health care systems.…”
Section: Discussionmentioning
confidence: 99%